Hot-pressing polyelectrolyte complexes into tunable dense saloplastics. (1st March 2022) - Krishna B, Ameya; Willott, Joshua D.; Lindhoud, Saskia; de Vos, Wiebe M.
Abstract: Salt-plasticized polyelectrolyte complexes of sodium polystrenesulfonate (Na-PSS) and polydiallyldimethylammonium chloride (PDADMAC) were found to be fully dense (non-porous) when hot-pressed under optimal conditions. The quality of these saloplastics is determined by the molecular weights of polyelectrolytes, the salt type and concentration, as well as processing conditions like pressure and temperature. Higher molecular weights give more compact precipitates that are easy to process while decreasing the molecular weight led to particulate ones. Both the type and concentration of salt on complex formation and doping are explored and are found to play an equally important role. The effects of individual hot-pressing parameters, namely, pressure and temperature are studied thoroughly, facilitating the formation of uniform free-standing films over a wide range of thicknesses from 8 μm to 1 mm. For the first time, saloplastics were studied as free-standing films that are dense even at the nanometer scale. In their dry states, they were brittle and strong, showing a uniform Young's modulus over a range of relevant thicknesses, while the wet states were rubbery and elastic, showing a decreasing trend with thickness. In the wet state, the inverse trend is due to the quicker drying of thin films. Within a single hot-pressing step, protruding shapes and structures from the surface were efficiently made at different length scales. Moreover, saloplastics were also successfully reinforced with thin woven and nonwoven fibers for enhanced tensile strengths, higher than conventional thermoplastics. Overall, this work demonstrates an easy approach to fabricate dense saloplastics and their unique mechanical properties. Graphical abstract: Image 1 Highlights: Na-PSS and PDADMAC complexes are varied using salt, concentration, molecular weight. Optimal complexes are hot-pressed into saloplastics and parameters are studied thoroughly. Freestanding and completely dense films over a wide range of thicknesses are made. Tensile tests in wet and dry states show the role of water, stability, strength. Reinforcements and profiles like chevrons are shown within single step hot-pressing.